2017
DOI: 10.21037/jss.2017.05.01
|View full text |Cite
|
Sign up to set email alerts
|

Elastic modulus in the selection of interbody implants

Abstract: The data generated in this paper may facilitate surgeons to make informed decisions on their choices of interbody implants with specific attention to the stiffness of the implant chosen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
76
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(76 citation statements)
references
References 20 publications
0
76
0
Order By: Relevance
“…The other geometrical pore sizes shown in Figure 16a and c has a negligible effect on bone growth. Implant failure due to Young's Moduli mismatch between the host bone is well documented (27,34). One of the most important challenges in this field is to tailor the desirable mechanical properties to minimise this failure.…”
Section: Discussionmentioning
confidence: 99%
“…The other geometrical pore sizes shown in Figure 16a and c has a negligible effect on bone growth. Implant failure due to Young's Moduli mismatch between the host bone is well documented (27,34). One of the most important challenges in this field is to tailor the desirable mechanical properties to minimise this failure.…”
Section: Discussionmentioning
confidence: 99%
“…One important property is elastic modulus, the measure of resistance to deformation in response to applied stress. Mismatches in the elastic modulus between the surrounding vertebral bodies and an implant may lead to issues such as subsidence and stress shielding [40]. Clinically, these issues can cause complications such as pseudarthrosis and non-unions.…”
Section: Engineering Studies Of Peek and Allograftmentioning
confidence: 99%
“…Thus, it is ideal for an implant to have a similar elastic modulus as native bone. Heary et al measured the elastic modulus and stiffness of various spinal interbody implants including neat and carbon-reinforced PEEK and cancellous and cortical bone [40]. The authors found that the elastic modulus of neat PEEK was similar to cancellous allograft bone, 3.84 and 3.78 GPa, respectively (Figure 1).…”
Section: Engineering Studies Of Peek and Allograftmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the characteristics of these crystalline alloys, instance of high elastic modulus, relative low abrasion resistance, and stress corrosion cracking lead to bone stress shielding. Compared with traditional crystalline metals, metallic glass has an amorphous structure, higher strength, lower Young's modulus, better wear resistance, higher corrosion resistance, and anti-fatigue performance for some Ti-, Zr-, Fe-base systems [5,6]. Over the course of the decades, many metallic glassy alloys have been developed using a wide range of components, including Pd-, Pt-, Zr-, Mg-, Ti-, Co-, and Au-base systems.…”
Section: Introductionmentioning
confidence: 99%